Natural gamma ray (NGR) data from core GLAD6 BOS04 5B - Mathias Vinnepand; Christian Zeeden; Thomas Wonik; William D Gosling; Anders Noren; Jochem Kück; Simona Pierdominici; Silke Voigt; Mehrdad Sadar Abadi; Arne Ulfers; Sylvester Danour; Kweku Afrifa; et al. (PANGAEA, 2024)
Here we present original Natural Gamma Ray (NGR) data from core GLAD6 BOS04 5B against depth that have been used as basis in the framework of the REFINE project aiming to establish an age-depth model that bases on a combination of cyclostratigraphy and correlation analyses. All core data (GLAD6 BOS04 5B) have been retrieved in a ~4 cm resolution by the Continental Scientific Drilling Facility at the University of Minnesota, USA using a Geotek MSCL-S multisensor core logger equipped with a 3-inch diameter NaI(Tl) detector housed in a 6-inch diameter lead shield. Measurement uncertainties range between 5 and 10%. All data are reported as total counts, integrating all emission counts over the gamma ray energy range between 0 and 3 MeV. For these measurements the archive core half has been used. Note that for correlation analyses the NGR data have been smoothed using a 35 point mean. The smoothed data can be also found at PANGEA. As correlation target, we used the Iberian Margin Sea Surface Temperatures. A suite of tiepoints has been created to bring the depth domain of core GLAD6 BOS04 5B to the age domain considering the age model of the Sea Surface Temperature record from the Iberian Margin. These tiepoints are also provided at doi:10.1594/PANGAEA.969454.